Carotid intima media thickness in patients with sporadic idiopathic hypoparathyroidism: a pilot study - Gupta, Yashdeep; Bhadada, Sanjay Kumar; Kalara, Naveen; Khurana, Dhiraj; Jain, Sanjay; Bhansali, Anil; Upreti, Vimal; Shah, Viral N (Endocrine Journal, 2012)
Alteration in calcium and phosphate levels predisposes to increase in carotid intima media thickness (CIMT) as in chronic kidney disease. However, information on CIMT changes is lacking in patients with sporadic idiopathic hypoparathyroidism (SIH) which is also a disorder of altered calcium and phosphate levels and hence, we planned this case-control study. In this study, we compared CIMT in 18 consecutive patients of SIH, with age and sex matched healthy subjects. CIMT was measured by B-mode ultrasonography by a single trained operator blinded to subject’s details. CIMT values in patients with SIH were significantly higher than healthy subjects (0.63±0.06 mm vs 0.47±0.07mm, p<0.001). Despite, healthy subjects had higher body mass index, higher low density lipoprotein cholesterol and fasting plasma glucose, CIMT was higher in subjects with SIH. Neither clinical nor biochemical parameters correlated with CIMT in patients with SIH except age. In conclusion, sporadic idiopathic hypoparathyroidism is associated with increased CIMT but biochemical parameters do not correlate with CIMT.